2021
DOI: 10.5114/ada.2020.96703
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean delivery and risk of childhood asthma development: meta-analysis

Abstract: Introduction: Several studies indicate that delivery by caesarean section may be one of the risk factors for the development of childhood asthma. Aim: A meta-analysis was carried out to establish the relationship between delivery by caesarean section and asthma in children. Material and methods: After a review of bibliographic databases, 41 articles were obtained and 12 of which were accepted for further analysis. The odds ratios (OR) included in the analysis were specified on the basis of data from the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
(45 reference statements)
0
10
0
3
Order By: Relevance
“…However, such findings remain inconclusive [ 8 , 13 , 14 , 15 , 45 ]. In this aspect, a recent meta-analysis demonstrated a higher probability of asthma in children born by caesarean section, both planned and unplanned, than those born vaginally [ 46 ]. However, this evidence should be taken with caution due to the considerable heterogeneity of the findings of the included studies [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such findings remain inconclusive [ 8 , 13 , 14 , 15 , 45 ]. In this aspect, a recent meta-analysis demonstrated a higher probability of asthma in children born by caesarean section, both planned and unplanned, than those born vaginally [ 46 ]. However, this evidence should be taken with caution due to the considerable heterogeneity of the findings of the included studies [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this aspect, a recent meta-analysis demonstrated a higher probability of asthma in children born by caesarean section, both planned and unplanned, than those born vaginally [ 46 ]. However, this evidence should be taken with caution due to the considerable heterogeneity of the findings of the included studies [ 46 ]. In accordance with this meta-analysis, we found that children born by caesarean section exhibited an 89% higher incidence of developing asthma at 2–5 years old than those delivered vaginally.…”
Section: Discussionmentioning
confidence: 99%
“…Temat wpływu cięcia cesarskiego na ryzyko rozwoju astmy u dzieci budzi jednak kontrowersje w świecie naukowym i wiele prac zaprzecza istnieniu takiej zależności [5,[18][19][20][21]. Meta-analiza z 2020 roku poddała analizie 12 badań przeprowadzonych w Europie w latach 1967-2012 i wykazała, że nie można jednoznacznie stwierdzić czy poród przez cięcie cesarskie zwiększa ryzyko astmy oskrzelowej u dzieci ze względu na dużą niejednorodność wyników tych badań.…”
Section: Badania Przeczące Zależności Pomiędzy Cesarskim Cięciem a Ro...unclassified
“…Powstało wiele prac próbujących zbadać powyższą zależność. Warto zatem przyjrzeć się im bliżej, ponieważ astma jest jedną z najczęstszych chorób przewlekłych dzieci, a niejasne czynniki predykcyjne są wciąż tematem dyskusji [18]. ASTMA Astma oskrzelowa to choroba, z powodu której coraz więcej dzieci wymaga hospitalizacji i jest częstsza pośród osób poniżej 18 roku życia [6].…”
Section: Introductionunclassified
“…Asthma is a disease whose etiology includes social determinants in addition to genetic and environmental factors [ 4 , 5 , 6 , 7 ]. They are related to environmental factors and are most often analyzed together.…”
Section: Introductionmentioning
confidence: 99%